The Role of Social Support in Promoting Adolescents’ Resilience during a Pandemic: Insights from Region XII, Philippines - Cris John Bryan C. Dela Cruz (East Asian Journal of Multidisciplinary Research, 2023)
The study determined the role of social support in promoting the resilience of 400 adolescents in Region XII, Philippines, during the COVID-19 pandemic. In analyzing the data, mean, standard deviation, Pearson product-moment correlation, and regression analysis were used. Results revealed that the level of social support indicated by emotional support and instrumental support is very high. The level of adolescent resilience is also very high, as indicated by novelty seeking, emotional regulation, and positive future orientation.  Social support helped promote the resilience of adolescents during the COVID-19 pandemic. Family, friends, and other significant individuals’ support is essential for alleviating distress and can be a vital component for fortifying interpersonal connections and relationships in order to build individuals' capacity to tolerate suffering and build resilience to cope with challenges and strains during the pandemic—a strong foundation for well-being throughout life.